2014
DOI: 10.1061/(asce)mt.1943-5533.0000954
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Emission Historic Index and Frequency Spectrum of Reinforced Concrete under Accelerated Corrosion

Abstract: The main cause of degradation for reinforced concrete (RC) structures is the corrosion of the steel reinforcement. Laboratory tests aimed at studying durability are typically accelerated to provide usable results within a reasonable period of time, and well-established electrochemical techniques are used for the assessment of corrosion. However, because these techniques are not suitable for continuous monitoring and are often intrusive, nondestructive testing (NDT) techniques are also suitable for monitoring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…In the final stages of the test CMA and LMA reach similar values, meaning that the historic index is approaching unity. This trend was also observed in [19] in a corrosion test.…”
Section: Historic Indexsupporting
confidence: 56%
See 2 more Smart Citations
“…In the final stages of the test CMA and LMA reach similar values, meaning that the historic index is approaching unity. This trend was also observed in [19] in a corrosion test.…”
Section: Historic Indexsupporting
confidence: 56%
“…Generally, it is assumed that 1-C 3 =C 1 /C 2 . In [19,31] the values C 3 =0.8 and C 1 =200 are suggested (thus implying C 2 =1000), with the rationale that the numerator should be the average signal strength of the last 20% or 200 hits, whichever is smaller. Given the low number of events recorded for the test setup described in this work, it was chosen to evaluate K considering C 3 =0.8 and C 1 =65, hence C 2 =325.…”
Section: Historic Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research on the feasibility of using AE to monitor corrosion in RC has been reported in the literature (e.g., Refs. [14][15][16][17][18]). However, corrosion of multiwire steel strands in PC may accrue from fundamentally different mechanisms such as stress corrosion cracking and crevice corrosion [8] at the wire impingement sites, potentially leading to more rapid deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this method is based on assuming uniform corrosion of the reinforcing steel, which may contradict with the actual corrosion process in existing structures [13]. It should also be mentioned that, the previously mentioned NDT methods are both not suitable for real-time monitoring and are typically intrusive [14].…”
Section: Introductionmentioning
confidence: 99%